Population Changes of Tylenchulus semipenetrans Under Localized Versus Uniform Drought in the Citrus Root Zone - Duncan, L W (Journal of nematology, 1996)
Population development of Tylenchulus semipenetrans in dry soil was investigated in a greenhouse study. Citrus seedlings were grown in sandy soil in vertical tubes with upper and lower sections. Nematode population densities in the upper tubes were measured at 16, 23, and 37 days, post-treatment. Three treatments consisted of i) irrigating both tubes when soil water potential reached -1 5 kPa (non-drought), ii) irrigating only the bottom tube (local drought), and iii) no irrigation (uniform drought). Soil water potential in the upper tubes did not differ under local and uniform drought during the first 16 days post-treatment, when it approached - 125 kPa. Thereafter, the water potential of soil under uniform drought continued to decrease, while that under local drought stabilized at approximately -150 kPa. Treatments had no consistent effects on female T. semipenetrans counts from soil or roots. However, after 37 days, numbers of eggs, juvenile, and male nematodes per gram of root under local drought were more than 2.4-fold greater than those under non-drought or uniform drought. Numbers of juvenile and male nematodes in soil were 6.5 times higher under local drought than under non-drought after 37 days. Nematodes did not survive in soil under uniform drought. Most of the eggs recovered on each date, from roots under local and non-drought, hatched within 35 days. Sixteen days of uniform drought reduced cumulative egg hatch to 51%, and almost no eggs hatched after 23 and 37 days of uniform drought. Thus, the response of T. semipenetrans to dry soil is fundamentally different, depending on whether all or part of the rhizosphere experiences drought. These data and field observations suggest that hydraulic lift via the root xylem may prolong the activity of some nematodes and possibly other rhizosphere-inhabiting organisms in dry soil